Strategic Alliance Networks and Innovation: A Deterministic and Voluntaristic View Combined - Gilsing, Victor A.; Lemmens, Charmianne E. A. V.; Duysters, Geert (Technology analysis & strategic management, 2007)
Over the past decades we have witnessed a tremendous growth in the number of strategic technology alliances and a growing importance of interfirm collaboration in the high-tech sectors. The literature on these topics has grown accordingly. In this respect, our paper serves two aims. One is to provide an overview of the consensus on key issues in this vast body of literature. Second is to identify some major gaps in this literature that may inform future research. In serving these aims, we first discuss the dominant structuralist perspective that stresses the role of embeddedness, but which also reflects a deterministic stance as if firms are subject to an exogenous structure. In contrast, we also explore a more voluntaristic view of how firms may possibly shape their network in view of achieving their strategic aims. This view also seems better able to capture change and network dynamics, an issue that has been largely ignored by the structuralist view.